MANAJEMEN PENGEMBANGAN KOMPETENSI PENDIDIK DI ERA SOCIETY 5.0: ANALISIS RELEVANSI DAN IMPLIKASINYA BAGI SUSTAINABLE DEVELOPMENT GOALS 4 - M. Dirham; M. Lathif Bashar; Erma Fatmawati; Khotimatus Sholikhah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The transformation of the educational paradigm in the Society 5.0 era demands the development of increasingly complex, technology-based, and sustainable competencies of educators. This condition requires a new strategic management approach to align the institution’s direction with educational goals. It also serves as an indicator of quality education as a goal of the Sustainable Development Goals. This study will examine how the concept of strategic management for developing educator competencies in the Society 5.0 era relates to variables such as strategic management implementation and assess its relevance and implications for achieving Sustainable Development Goal 4. This study uses a qualitative study-based approach with instruments of reduction techniques, content analysis, and triangulation. The results of the study is: (1) Indonesian educators tend to remain unprepared to address the competency challenges arising from educational transformation in the current era, and (2) the management approach that must be adopted smart management by bay data-based, encompassingin planning, organizing, directing, controlling, and supervising (3) competency development is implemented through the strengthening of Continuous Professional Development, digitizing learning, developing professional communities, innovative learning models, data-based assessments, teaching concepts and methods based on the integration of education and technology (4) The implementation of competency development demonstrates significant relevance to achieving SDG 4 indicators, such as learning quality, access to inclusive education, educators’ technical skills and professionalism, a humanistic and sustainable learning environment, and the quality of educator competency. Thus, developing educator competency in the Society 5.0 era is a strategic foundation for realizing quality and sustainable education.